The books of the dead revisited: mortality and morbidity in the German colonies of southern Brazil, 1850-1880 - João Biehl; Miquéias Henrique Mugge; Ana Maria Goldani (História, Ciências, Saúde: Manguinhos)
Abstract Examines mortality and morbidity in São Leopoldo/RS (1850-1880). Our interdisciplinary study is based on the Gemeindebücher (parish registers) produced by Lutheran communities. These “community books” reveal high rates of fertility and premature death. Infant mortality and maternal death assailed everyday life. Over half of all deaths were of infants and children. Of ten funerals, seven were for children and adults of reproductive and military age. This article contributes to debates over environmental, social and political determinants of mortality and people’s arts of living and healing in proto-statistical Brazil.